Joint Design of Binary Probing Sequence Sets and Receive Filter Banks for MIMO PMCW Radar - Chen, Yutao; Cheng, Yuanbo; Lin, Ronghao; So, Hing Cheung; Li, Jian (IEEE transactions on signal processing, 2024)
The joint design of binary probing sequence (BPS) sets and receive filter banks is critical to the performance of low-cost multiple-input multiple-output (MIMO) phase-modulated continuous wave (PMCW) radar for autonomous driving applications. Compared to the commonly used matched receive filter banks in MIMO PMCW radar, mismatched receive filter (MMRF) banks can attain much lower sidelobe levels due to its higher degrees-of-freedom, at the cost of slight signal-to-noise ratio (SNR) reduction. We focus herein on using computational methods, with statistically independent random initializations, to jointly design BPS sets and MMRF banks with ample diversity and arbitrary lengths. Our approach specifically caters to the needs arising from autonomous driving applications and has not been studied before. Theoretical analyses of the proposed algorithms, including convergence properties and losses of SNR due to mismatched filtering, are provided. The effectivenesses of our methods is also demonstrated via numerical examples.